The Application of Patchwork Techniques on Production Waste Fabric in A Shoulder Bag Design - Aurelia Arsanti, Danella; Judianto, Oskar (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2025)
Due to the existence of the fast fashion industry and companies that produce clothes quickly and offer them at relatively affordable prices, the accumulation of textile waste has become a pollution problem. As clothing production increases, unused fabric scraps are generated. The waste produced is often not utilized properly and ends up in landfills. Many people use leftover fabric to make various types of models. However, the results obtained from using leftover fabric materials are rarely applied in many activities, because the designs obtained from using leftover fabric materials are not suitable for everyday use. Therefore, this design advances the development of shoulder bag design. Using the patchwork technique to manage fabric scraps makes it easier to combine materials. We chose denim fabric to complement the design and create a casual and unique shoulder bag design. That way, products made using leftover fabric can be used by everyday users.